SOCIO-PEDAGOGICAL ASPECT OF THE PROBLEM OF «SOUL ECOLOGY» OF CHILDREN AT RISK - Burenina, Svetlana; Kalinina, Svetlana; Petrash, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article is devoted to the search for ways of spiritual enrichment of the soul of children at risk. The authors actualize the problem of" impoverishment" of the soul and justify the socio-pedagogical conditions of its ecology. The purpose of the work was to study the problem of "soul ecology" and experimental study of value orientations of children at risk, filling both the external and internal world of the child. The paper used theoretical and empirical research methods. As the results of the study show, the most significant are material values. Therefore, it is important to create a system of spiritual and moral education of children at risk and teach them spiritual existence by gaining personal meaning in the social situation in which they find themselves.